Thromboembolic characteristics and role of anticoagulation in long-standing Fontan circulation - Mechthild Westhoff-Bleck (International Journal of Cardiology Congenital Heart Disease, 2022)
Introduction: The risk of thromboembolism increases with duration of Fontan circulation. Preventive drug strategies are still discussed controversially. We aimed to characterize clinical relevant thromboembolism in long-standing Fontan circulation and to analyse the protective effect of Acetylsalicylic acid (ASA) and Vitamin K Antagonists (VKA). Method: 78 patients (age ≥16 years) were included (mean age 20.7 ± 5.7 years; 51 male). Last medication and duration of therapy were documented. Perioperative events were excluded. Mean time of Fontan circulation was 21.1 ± 6.3 years, mean observation time 8.1 ± 5.6 years. Results: 44 patients were on VKA, 15 on ASA, 19 without treatment. Fifteen (19.2%) patients experienced thromboembolism. Nine patients had deep venous thromboses, among these five experienced pulmonary embolism. Four patients presented with supraventricular tachycardia (SVT), two with cerebral embolism and thrombus within the Fontan tunnel respectively. Two patients had an isolated thrombus in the Fontan tunnel. Time of Fontan circulation was significantly longer in thromboembolism (25.6 ± 8.3 years vs. 20.0 ± 5.2 years, p < 0.001). NYHA-class was worse (p = 0.03). Lacking treatment [OR 10.2 (95%CI 1.5–66.3)] and ASA [OR 1.25(95%CI)1.06–1.22] carried significantly higher risk of thromboembolism than VKA [OR 0.17 (95%CI 0.09–0.33)]. Kaplan-Meier analysis did n't differ in lacking treatment versus ASA (p = 0.2). VKA showed the best net-benefit regarding thromboembolism/bleeding complications (VKA: 11.4%, ASA 25%, VKA vs. lacking treatment 63.2%: p < 0.001). Conclusion: In long-standing Fontan circulation anticoagulation appears to be a safe treatment option to prevent late thromboembolism mainly caused by deep vein thrombosis and intracardiac thrombus formation associated with SVT.